Retaining structures proceedings of the conference Retaining structures, organized by the Institution of Civil Engineers and held at Robinson College, Cambridge on 20-23 July 1992 - Clayton, C. R. I. (Thomas Telford, 1993)
For practising civil and structural engineers in the field of general earth-retaining structure theory, this work presents the results of many case studies of actual retaining wall analysis, design, and construction. It also includes fundamental papers dealing with the effects of groundwater on passive earth pressure, and other related topics.